2022
DOI: 10.3390/ijerph19010611
|View full text |Cite
|
Sign up to set email alerts
|

Personal Exposure to Fine Particles (PM2.5) in Northwest Africa: Case of the Urban City of Bamako in Mali

Abstract: Personal exposure to particulate matter (PM) from anthropogenic activities is a major concern in African countries, including Mali. However, knowledge of particulates is scant. This study was undertaken to characterize personal exposure to PM2.5 microns or less in diameter (PM2.5) in the city of Bamako in Mali. The exposure to PM2.5, through daily activities was observed from September 2020 to February 2021. Participants wore palm-sized optical PM2.5 sensors on their chest during their daily activities. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Among the basic parameters that directly affect the level of influence on humans and technical systems are the shape, size, and dimensions of particles, alongside the chemical composition of particulate matter. The behaviour, deposition, and fate of each particle after entering the human respiratory system depend on their natures and the specified parameters [4][5][6]. Based on this, we can conclude that the importance of measuring particle size and shape distribution lies in the fact that the properties of dispersed materials depend on the uniformity of their distribution.…”
Section: Introductionmentioning
confidence: 86%
“…Among the basic parameters that directly affect the level of influence on humans and technical systems are the shape, size, and dimensions of particles, alongside the chemical composition of particulate matter. The behaviour, deposition, and fate of each particle after entering the human respiratory system depend on their natures and the specified parameters [4][5][6]. Based on this, we can conclude that the importance of measuring particle size and shape distribution lies in the fact that the properties of dispersed materials depend on the uniformity of their distribution.…”
Section: Introductionmentioning
confidence: 86%
“…In addition to vehicular emission and other sources already mentioned, Sahelian dust is a major contributor to air pollution in the high-latitude Sahel countries such as Mali, Mauritania, Burkina Faso and, to a lesser extent, Senegal (see Table 1) ( [45][46][47][48][49][50][51][52][53]). Studies also shown that aerosols and other suspended particulates tend to vary seasonally across the West African region, albeit with more concentrations in the harmattan/dry periods than the wet season [48][49][50][51][52] (not reflected in Table 1). However, the pollution level also has a highly significant spatial distribution across the sub-region.…”
Section: Pollutant Sources Levels and Distributionmentioning
confidence: 99%
“…However, the pollution level also has a highly significant spatial distribution across the sub-region. Studies also shown that aerosols and other suspended particulates tend to vary seasonally across the West African region, albeit with more concentrations in the harmattan/dry periods than the wet season [48][49][50][51][52] (not reflected in Table 1). However, the pollution level also has a highly significant spatial distribution across the sub-region.…”
Section: Pollutant Sources Levels and Distributionmentioning
confidence: 99%
“…Some of these studies have highlighted the oxidative and inammatory effect of PM 2.5 aerosol on human bronchial epithelial cells. [6][7][8][9][10][11][12] The cardiovascular health effects have also been evaluated in Accra. 13 The PM 2.5 data required for these studies were obtained from photometric measurements 14,15 and from modelling or eld campaign observations.…”
Section: Introductionmentioning
confidence: 99%